A Concept Paper of Balanced Scorecard for New Product Development - Zhengxiaoming, Aminaimu; Fernando, Yudi (Universiti Malaysia Pahang, 2019)
The aim of this study is to review the concept of Balanced Scorecard (BSC) technique to develop a new product. BSC as a strategic performance tool has received closed attention by many organizations worldwide, however, the implementation has been limited. The globalization and economic upheaval have increased the challenges to the executives face and therefore need to find the right tools to overcome the challenges. The current paper focuses on review of literature on the importance of BSC towards new product development and business performance. This paper suggests that the 4th generation balance scorecard leads the combination of management system and performance measurement that brings up one big strategy maps, and possibly will use widely to satisfy the customer demands. This paper discusses on the current issues and emerging importance of BSC literature and suggests fruitful areas for further study.